(untitled) (Revista Direito em Debate, 2022)
The article analyzes blood transfusion in Jehovah’s Witnesses, who has not complete discernment. It concentrates on the specific case of Adam Henry, a character of Ian McEwan’s novel The Children Act. Inductive method was used along with the techniques of bibliographic research, the analysis of the legislation and the decisions and registration of the research. McEwan’s novel portrays the daily life of woman Judge Fiona Maye, of the High Court of London, and the conflicts she has to confront regarding her life, both personal and professional. Mrs. Maye will preside over teenager Adam Henry’s case, who suffers from leukemia. Due to the severity of his disease, the physicians decide to carry out blood transfusion. As both Adam and his parents are Jehovah’s Witnesses, the medical procedure is not allowed by the family. However, despite the boy’s maturity, the judge decides that the hospital will perform the transfusion, relying on fundamental rights such as Adam’s rights to life, health and physical integrity. Conclusion indicates that Mrs. Maye’s decision takes Adam’s welfare and his chance to live into consideration. Besides, it highlights the State’s responsibility to protect the boy’s physical integrity as he is a minor.